2009
DOI: 10.1007/s12602-009-9029-4
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Extracts from Cultures of Certain Lactobacilli Inhibit Helicobacter pylori

Abstract: Helicobacter pylori inhibition by probiotic lactobacilli has been observed in vitro and in vivo. Carefully selected probiotic Lactobacillus strains could therefore play an important role in the treatment of H. pylori infection and eradication. However, the underlying mechanism for this inhibition is not clear. The aim of this study was to examine if peptide extracts, containing bacteriocins or other antibacterial peptides, from six Lactobacillus cultures (Lactobacillus acidophilus La1, Lactobacillus amylovorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…1088 as suggested for anti- H. pylori activity of L. johnsonii La1 (De Vuyst et al. 2010 ). The clinical effectiveness of lactobacilli is controversial depending on the strains used for studies, but some promising results have been reported regarding L. gasseri OLL2716 (Sakamoto et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1088 as suggested for anti- H. pylori activity of L. johnsonii La1 (De Vuyst et al. 2010 ). The clinical effectiveness of lactobacilli is controversial depending on the strains used for studies, but some promising results have been reported regarding L. gasseri OLL2716 (Sakamoto et al.…”
Section: Discussionmentioning
confidence: 96%
“… 2008 ; De Vuyst et al. 2010 ). Although competitive colonization and production of various compounds having microbial activities (organic acids, bacteriocins, hydrogen peroxide, carbon dioxide, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity of LS-8-25 was assayed by a modified method (Avonts, Uytven, & Vuyst, 2004;De Vuyst, Vincent, Makras, Leroy, & Pot, 2009). Briefly, equal volumes (50μL) of two-fold dilutions sample and indicators (10 6 CFU/mL) were mixed in 96 well plate (Costar, Corning, USA) and incubated at 37 °C for 24 h, E. coli and S. aureus were used as indicators.…”
Section: Antibacterial Activitymentioning
confidence: 99%